Effects of tectonic stresses and structural planes on slope deformation and stability at the Buzhaoba open pit mine, China - Chen, Shuzhao; Goh, Thian Lai; Liu, Han; Tovele, Gerson. S.V. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Tectonic stresses and structural planes are key factors that affect slope stability. The studies of the effect mechanism of the two factors on the slope deformation and instability have an important value for realizing an accurate evaluation of slope stability. The deformation and landslide problems of the west slope at the Buzhaoba open pit mine were analyzed. Tectonic stresses and structural planes were confirmed as the main factors of long-term deformation of the slope. According to an analysis of the regional structure, the principal stress direction of the Buzhaoba mine was 123° and the slope sliding mode and discriminant conditions were determined under the influence of tectonic stress. The principal stress direction was verified by comparison with the results of displacement monitoring and stability analysis of the slope. The factor of safety of the slope is 1.29 when considering tectonic stress and reduces by 7.19% when tectonic stress is not considered.